Does physiological-based cord clamping improve cerebral tissue oxygenation and perfusion in healthy term neonates? – A randomized controlled trial - Schwaberger, Bernhard; Ribitsch, Mirjam; Pichler, Gerhard; Krainer, Marlies; Avian, Alexander; Baik-Schneditz, Nariae; Ziehenberger, Evelyn; Mileder, Lukas Peter; Martensen, Johann; Mattersberger, Christian; Wolfsberger, Christina Helene; Urlesberger, Berndt (Frontiers in Pediatrics, 2023)
Objectives To evaluate cerebral tissue oxygenation index (cTOI) during neonatal transition in a group of healthy full-term neonates receiving either a physiological-based approach of deferred cord clamping (CC) after the onset of stable regular breathing (PBCC group) or a standard approach of time-based CC < 1 min (control group). Secondary aim was to evaluate changes in cerebral blood volume (ΔCBV), peripheral arterial oxygen saturation (SpO2) and heart rate (HR) in those neonates. Materials and Methods We conducted a randomized controlled trial (clinicaltrials.gov: NCT02763436) including vaginally delivered healthy full-term neonates. Continuous measurements of cTOI and ΔCBV using near-infrared spectroscopy, and of SpO2 and HR using pulse oximetry were performed within the first 15 min after birth. Data of each minute of the PBCC group were compared to those of the control group. Results A total of 71 full-term neonates (PBCC: n = 35, control: n = 36) with a mean (SD) gestational age of 40.0 (1.0) weeks and a birth weight of 3,479 (424) grams were included. Median (IQR) time of CC was 275 (197–345) seconds and 58 (35–86) seconds in the PBCC and control group, respectively (p < 0.001). There were no significant differences between the two groups regarding cTOI (p = 0.319), ΔCBV (p = 0.814), SpO2 (p = 0.322) and HR (p = 0.878) during the first 15 min after birth. Conclusion There were no significant differences in the course of cTOI as well as ΔCBV, SpO2 and HR during the first 15 min after birth in a group of healthy full-term neonates, who received either deferred CC after the onset of stable regular breathing or standard CC < 1 min. Thus, deferring CC ≥ 1 min following a physiological-based approach offers no benefits regarding cerebral tissue oxygenation and perfusion after uncomplicated vaginal delivery compared to a time-based CC approach.